Qutrit Control for Bucket Brigade RAM Using Transmon Systems - Lazaros Spyridopoulos; Dimitris Ntalaperas; Nikos Konofaos (Applied Sciences)
Qudits allow the encoding and manipulation of additional quantum information compared to that stored to a two-level qubit system. Although manipulations of qudit states are generally more complex and can introduce extra sources of noise, qudits can still be used in a number of applications when this error can be kept sufficiently low. One such application is the case of the Bucket Brigade Algorithm for realizing a Quantum RAM (QRAM), which inherently uses qutrits for encoding the state of address switches. In this paper, we study a methodology for qutrit manipulation that leverages efficient encoding techniques and pulse calibration methods for the case of transmon systems. The methodology employs an encoding scheme that allows the execution of controlled operations, using the subspace spanned by the two lowest levels of the transmon; we show how this scheme can be used for generating one- and two-qutrit gates by leveraging the Qiskit and Boulder Opal frameworks to compute the parameters of pulses that implement the quantum gates that are used by the BBA. For this type of gate, simulations show that the pulses perform the required operations with a low infidelity when errors introduced by the qutrit Hamiltonian dynamics are considered.